Evaluation of Nutritional and Physico-Chemical Properties of Several Selected Fruits in Bangladesh - Haque, M Nazmul; Saha, Barun Kanti; Karim, M Rezaul; Bhuiyan, M Nurul Huda (Bangladesh Journal of Scientific and Industrial Research, 2010)
In this study , various parameters on nutritional and physico-chemical characteristics of eight different fruits (five minor and three major fruits), namely melon, guava, papaya, karanda, burmese-grape, velvet apple, wood-apple and pomelo of Bangladesh were analyzed to determine the edible portion of whole fruit, pH, titratable acidity, moisture, total soluble solid, reducing sugar, total sugar, crude fibre, total carbohydrate, total protein, total fat, total energy, vitamin C, ash , sodium, potassium, iron and arsenic content. The largest amount of iron, 5.34 mg/100g was observed in Burmese-grape. The pomelo contained the highest amount of potassium, 233.07mg/100g and the lowest amount of sodium, 2.25mg/100g. The maximum amount of fibre, 6.21% was found in wood-apple and the richest quantity of vitamin C, 80mg/100g was found in guava. In general arsenic was not found in karanda, burmese grape, guava, pomelo, wood-apple, and papaya and only negligible amount of arsenic was revealed in velvet apple, 0.01 mg/kg, followed by melon, 0.005 mg/kg. Key words: Minor and major fruits, Malnutrition, Micronutrient, Bangladesh DOI: 10.3329/bjsir.v44i3.4410 Bangladesh J. Sci. Ind. Res. 44(3),353-358, 2009